The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0195956
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic flux blockage by accumulation of weakly basic tenovins leads to elimination of B-Raf mutant tumour cells that survive vemurafenib

Abstract: Tenovin-6 is the most studied member of a family of small molecules with antitumour activity in vivo. Previously, it has been determined that part of the effects of tenovin-6 associate with its ability to inhibit SirT1 and activate p53. However, tenovin-6 has also been shown to modulate autophagic flux. Here we show that blockage of autophagic flux occurs in a variety of cell lines in response to certain tenovins, that autophagy blockage occurs regardless of the effect of tenovins on SirT1 or p53, and that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Our previous studies used the SIRT1 inhibitor, Tenovin 30 (TV30), which has recently been shown to have additional autophagy inhibitory effects that could affect mitochondrial mass and function independently of SIRT1. Therefore, for the current studies, we used a congener, Tenovin 39OH (TV39OH), which retains SIRT1 inhibitory effects, but does not have autophagy inhibitory properties (35). CML BM CD34 + cells were treated with TV39OH (5 μM), the TKI NIL (1 μM), or a combination.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies used the SIRT1 inhibitor, Tenovin 30 (TV30), which has recently been shown to have additional autophagy inhibitory effects that could affect mitochondrial mass and function independently of SIRT1. Therefore, for the current studies, we used a congener, Tenovin 39OH (TV39OH), which retains SIRT1 inhibitory effects, but does not have autophagy inhibitory properties (35). CML BM CD34 + cells were treated with TV39OH (5 μM), the TKI NIL (1 μM), or a combination.…”
Section: Discussionmentioning
confidence: 99%
“…Other SirT1 inhibitors such as the tenovins and inhauzin have been described to increase p53 levels and function (Lain et al, 2008; Zhang et al, 2012). However, at least in the case of the tenovins, the activation of p53 may be due to additional modes of action of these molecules as it has been shown previously that certain tenovins are capable of demonstrating target engagement with SirT1 without cells responding with a rise in levels or activity of p53 (Ladds et al, 2018a).…”
Section: Targeting Posttranslational Modifications Of P53mentioning
confidence: 99%
“…S1, A and B ). This modeling study and its correlation with the results seen in both the enzymatic assay and thermal shift data ( 11 , 14 , 18 ) served as a proof of principle for modeling the interactions of the tenovins with other targets.…”
Section: Resultsmentioning
confidence: 72%
“…We previously conducted a target confirmation study with the tenovins (see Table 1 for structures) by examining their ability to interact with SirT1 in cells using a cellular thermal shift assay (CETSA) to ensure that the compound series interacted with its purported target ( 14 ). In the present study, we have used molecular modeling to examine the energetics of interactions of these molecules in their interaction with SirT1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation